Functional evidence of mTORβ splice variant involvement in the pathogenesis of congenital heart defects. Issue 3 (30th November 2020) - Gentile, Mattia; Ranieri, Carlotta; Loconte, Daria C.; Ponzi, Emanuela; Ficarella, Romina; Volpe, Paolo; Scalzo, Gabriele; Lepore Signorile, Martina; Grossi, Valentina; Cordella, Angela; Ventola, Giovanna Maria; Susca, Francesco C.; et al.
Abstract: mTOR dysregulation has been described in pathological conditions, such as cardiovascular and overgrowth disorders. Here we report on the first case of a patient with a complex congenital heart disease and an interstitial duplication in the short arm of chromosome 1, encompassing part of the mTOR gene. Our results suggest that an intragenic mTOR microduplication might play a role in the pathogenesis of non‐syndromic congenital heart defects (CHDs) due to an upregulation of mTOR/Rictor and consequently an increased phosphorylation of PI3K/AKT and MEK/ERK signaling pathways in patient‐derived amniocytes. This is the first report which shows a causative role of intragenic mTOR microduplication in the etiology of an isolated complex CHD. Abstract :